(untitled) (AI Governance and Society Journal p-ISSN 3117-6097 and e-ISSN 3117-6100, 2025)
As artificial intelligence (AI) continues to reshape industries, governance systems, and social interactions, the ethical implications of its deployment have become a pressing global concern. The rapid evolution of AI technologies has outpaced the development of comprehensive ethical and governance frameworks, leading to challenges related to bias, accountability, transparency, and privacy. This paper explores the necessity of ethical frameworks in AI governance and proposes a multi-dimensional approach integrating law, ethics, and technology. It presents a case study of AI ethics implementation in public sector decision-making, supported by data from expert surveys and stakeholder questionnaires. The results highlight that robust ethical frameworks, when embedded into governance structures, foster public trust and ensure responsible AI usage. The paper concludes by suggesting a global model for ethical AI governance grounded in fairness, transparency, and accountability.